Hidden treasures: Brazilian plants collected by prince maximilian zu Wied held in the national herbarium of Victoria (MEL) - Gallagher, C. L.; De Moraes, P. L.R. [UNESP] (My University, 2014)
The 'discovery' at MEL of some of the earliest extant herbarium specimens known from Brazil is detailed. The history and significance of 325 specimens collected by M.A.P. zu Wied in 1815-1817 is outlined and used to illustrate the value and relevance of the largely uncurated Sonder herbarium and wider foreign collection at MEL.
Keywords: Brazil; Sonder herbarium; Wied-neuwied